2005
DOI: 10.1097/01.blo.0000187059.19949.cd
|View full text |Cite
|
Sign up to set email alerts
|

Revision of the Patella with Deficient Bone Using a Biconvex Component

Abstract: Retrospective study, Level IV-1 (case study). See the Guidelines for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 11 publications
0
15
0
1
Order By: Relevance
“…The status of patellar bone stock often dictated which revision patellar component was used. Thinner residual patellae were most commonly revised with a Genesis Biconvex (Smith and Nephew, Memphis, TN) [27]. Residual patellar thickness is routinely measured intraoperatively and in our experience, the minimal patellar thickness with an intact peripheral cortical rim necessary to accommodate the Genesis Biconvex is 4 to 5 mm.…”
Section: Methodsmentioning
confidence: 91%
“…The status of patellar bone stock often dictated which revision patellar component was used. Thinner residual patellae were most commonly revised with a Genesis Biconvex (Smith and Nephew, Memphis, TN) [27]. Residual patellar thickness is routinely measured intraoperatively and in our experience, the minimal patellar thickness with an intact peripheral cortical rim necessary to accommodate the Genesis Biconvex is 4 to 5 mm.…”
Section: Methodsmentioning
confidence: 91%
“…The importance of the patella in contributing to knee kinematics has been well established [40]; therefore, authors have recommended the complete abandonment of patellectomy in revision TKA and recommended either a patellar bone augmentation procedure in an attempt to restore the poor patella bone stock or a patellar resection arthroplasty (patelloplasty) procedure [4,19,21]. In more recent reports, severe bone-deficient patellae with less than 10 to 12 mm of cortical bone have been managed successfully using either an inlay-type cemented, all-polyethylene, domeshaped biconvex component or a porous trabecular metal (tantalum) component [23,30,32].…”
Section: Patellar Component Revision Optionsmentioning
confidence: 99%
“…A patella remnant composed of a 5-to 10-mm thick bony shell can typically accommodate the biconvex patellar prosthesis. Maheshwer et al [30] reported on 20 patellar revisions in which the Genesis Biconvex patella (Smith and Nephew, Inc) was implanted into a patellar remnant with an average minimal thickness of 6.5 mm (range, 4.5-10 mm). At a minimum followup of 24 months (average, 34 months; range, 24-65 months), these authors reported improved Knee Society knee scores and satisfactory knee range of motion (average, 105°) without any patellar fractures or other complications requiring additional surgery [30].…”
Section: All-polyethylene Biconvex Patellar Prosthesismentioning
confidence: 99%
See 2 more Smart Citations